Highly stable and biocompatible zwitterionic dendrimer-encapsulated palladium nanoparticles that maintain their catalytic activity in bacterial solution. (14th November 2018) - Wang, Longgang; Zhang, Jin; Guo, Xiaolei; Chen, Shengfu; Cui, Yanshuai; Yu, Qingyu; Yang, Lubin; Sun, Haotian; Gao, Dawei; Xie, Danyang
Abstract : This study offers a method for constructing an artificial enzyme (Pd n -G5MC), which maintains its catalytic efficiency in bacterial solution. Abstract : The development of artificial enzymes to mimic the properties of natural enzymes has been receiving much research interest. Herein, zwitterionic dendrimer-encapsulated palladium nanoparticles (Pd n -G5MC NPs) were constructed to investigate their biocompatibility and catalytic ability in bacterial solution. Zwitterionic dendrimer templates were synthesized via the surface modification of generation 5 polyamidoamine (G5 PAMAM) dendrimers with maleic anhydride and cysteamine. The Pd n -G5MC NPs were prepared by incubation of the templates with disodium tetrachloropalladate, followed by reduction with sodium borohydride. The Pd n -G5MC NPs displayed high stability, biocompatibility, and catalytic efficiency. Remarkably, Pd55 -G5MC NPs maintained high stability over a broad pH range (4–9) and high salt concentration (up to 20%) within 24 h. Pd55 -G5MC NPs did not show noticeable cytotoxicity to HUVEC cells or HeLa cells at a concentration of 500 μg mL −1, while G5 PAMAM dendrimer-encapsulated palladium nanoparticles (Pd55 -G5 NPs) had obvious cytotoxicity (∼10% cell viability). Furthermore, Pd55 -G5 NPs had a minimal inhibitory concentration (MIC) of 400 μg mL −1, while Pd n -G5MC NPs did not show any bacterial growth inhibition at the same concentration. More importantly, Pd55 -G5MC NPs maintained their catalytic activity in bacterial solution compared to Pd55 -G5 NPs. The apparent rate constant k app is dependent on the concentration of morin or hydrogen peroxide. All the forementioned properties suggested that Pd n -G5MC NPs could be employed in bio-related systems in nature.